Insights of ESL students' peer review in writing class / Norasyikin Abdul Malik... [et al.] - Abdul Malik, Norasyikin; Mohd Nasir, Nur Fatima Wahida; Hasni, Nurul Ain; Kasmaruddin, Nurhidha Irawaty (UiTM Cawangan Johor, 2019)
The practice of peer review as a method of evaluation is believed to be helpful in learning and is favoured especially by educators in higher education settings. Constraints resulting from examination oriented subjects and the large number of students in each class limit the educators' ability to give personal feedback to each student, forcing them to opt for peer review as an alternative for evaluation. Thus, this study aims to better learn the students' views on the implementation of peer review in their writing class and also to recognise the strengths and weaknesses according to the perspectives raised by these students. Four interview questions were crafted to investigate the students' views on peer review activity in writing class. Semi-structured interviews were carried out, recorded, transcribed and analysed. Textual data, audio recordings and interviews from 18 individuals from the third semester of diploma students revealed that peer review activity made them to be aware of the strengths and weaknesses of their essays. However, some of them viewed peer review as a platform to critic or being criticised, rather than as a learning tool. The findings also revealed that despite the positive feedback of peer review to their writings, they preferred the lecturer's feedback more. A majority of these students suggested that lecturer's feedback is still important other than having the peer review activity for the class as a source of writing feedback.